Allopurinol use and the risk of cataract formation. Issue 3 (March 1989) - Clair, W K; Chylack, L T; Cook, E F; Goldman, L
Abstract : Several reports have suggested an association between chronic allopurinol ingestion and cortical and subcapsular cataract formation. To examine this possibility we identified 51 allopurinol users and compared their lenses with those of 76 patients who did not use allopurinol. The existence of lens opacities and the level of visual acuity were assessed by review of medical records or by prospective ophthalmic examinations; in both phases of the study the examiners were blinded as to the patient's use or non-use of allopurinol. Three different outcomes were considered: formation of any cataract, formation of a posterior subcapsular cataract, and formation of a cataract contributing to a corrected visual acuity of 20/30 or worse. The risk ratio for the formation of any cataract was 1.3 (95% confidence interval: 0.8, 2.0), the risk ratio for the formation of a posterior subcapsular cataract was 0.9 (0.3, 2.0), and the risk ratio for the formation of a cataract contributing to a loss of visual acuity was 1.3 (0.6, 2.9). None of these risk ratios was changed appreciably after controlling for age, sex, hypertension, or diabetes. Thus, after a mean of 6.9 years of allopurinol use, we found no evidence to confirm that allopurinol users were at higher risk of acquiring cataracts.